The Impact of Genome Region of Difference 4 (RD4) on Mycobacterial Virulence and BCG Efficacy - Ru, Huanwei; Liu, Xiaojia; Lin, Chen; Yang, Jingyan; Chen, Fuzeng; Sun, Ruifeng; Zhang, Lu; Liu, Jun (Frontiers in Cellular and Infection Microbiology, 2017)
Comparative genome analyses have revealed a number of regions of difference (RD) among mycobacterial species. The functional consequences of most of these genome variations have not been studied. RD4, which encompasses Rv1506c-Rv1516c of Mycobacterium tuberculosis (M. tb) H37Rv, is absent in the closely related Mycobacterium bovis and M. bovis Bacille Calmette-Guérin (BCG). On the other hand, we previously found that Mycobacterium marinum has an extended RD4 which includes a number of genes involved in the biosynthesis of lipooligosaccharides (LOSs). As such, there appears to be a gradual decay of RD4 in mycobacterial genomes in the order of M. marinum, M. tb, and M. bovis (including BCG). To understand the potential effect of RD4 on mycobacterial virulence, in this study, we cloned the entire (Rv1501–1516c) and partial (Rv1501–1508c) RD4 into an integrating vector. These constructs were introduced to M. bovis BCG and M. marinum and the virulence of the RD4 knock-in strains were evaluated in the SCID mice and zebrafish infection models, respectively. BCG containing the entire RD4 exhibited similar levels of virulence to the parental strain but BCG containing partial RD4 (Rv1501–Rv1508c) was more attenuated. Similarly, zebrafish infection experiments showed that addition of partial RD4 also appeared to attenuate the virulence of M. marinum. However, M. marinum containing entire RD4 was more virulent than the wild type strain. Interestingly, BCG strains containing the entire or partial RD4 exhibited better protection of zebrafish against M. marinum challenge than the parental BCG. Taken together, our data suggest that RD4 plays a role in mycobacterial virulence and that RD4 knock-in BCG strains confer improved protection. Our study has provided new insights into the biological function of RD4 and evolution of mycobacterial genomes.